Ivan Pavlov : exploring the animal machine - Todes, Daniel Philip (Oxford portraits in science., 2000)
A biography of the Russian physiologist who won the Nobel Prize for Medicine in 1904 for research on the digestive system and is perhaps best known for his research on dogs.